Human Capital Investment Development Strategy in Indonesia - Veramika br Sembiring (Journal of Research in Business, Economics, and Education, 2021)
In its implementation, increasing human resources can also be done through educational partnerships to improve formal education, which is still so low. For this reason, all parties, both private and bureaucrats, jointly manage human resources as "Human Investment" to improve the quality of our human resources, which are still so low that they can become more competitive and have "Intellectual Capital". Human resource quality improvement programs through education will provide benefits to organizations. This approach begins from a current strategic driven. To be effective, the approach must be based on accurate problem diagnosis and analysis of plan alternatives. This approach will make it easier for the organization to focus more accurately on a particular part or skill that is needed. What needs to be considered in HR planning is environmental observation, both internal and external. To improve the quality of human resources in the future, all parties, both private and bureaucrats, collectively through a partnership program to manage human resources as "Human Investment" to improve the quality of our human resources through education so that they can become more competitive and have "Intellectual Capital. Increasing human resources through education needs to be done through political, economic, legal, socio-cultural, and administrative / managerial approaches.